The Concept of ‘Supernaturalism’ in British and American Fiction: A Comparative Study - Ali, Areej Mohammed Mubarak (Journal of Humanities & Social Sciences, 2024)
Supernatural fiction invites the reader to a world of mystery and imagination raising questions and sometimes doubts about the reality of this world. As it tempts the reader to explore the “unknown”, it tends to emphasize the possibility of the existence of vague worlds and issues beyond human mind and science. However, this possibility remains a hypothesis because it is always accompanied by a feeling of “uncertainty” which raises our doubts and made us skeptic about the existence and reality of this world. The same supernatural literary works tackle social, religious, and scientific issues as well as posing questions about its reliability which is another form of skepticism. This research argues that Skepticism is not far from the Gothic literary works, it presents various cases of “skepticism” in different supernatural literary works: The Rime of the ancient Mariner (1798), Frankenstein (1818), Young Goodman Brown (1835), The Fall of the House of Usher (1839). Each case of skepticism differs from the other in its form, the circumstances that created it, the purpose behind using it, and the conclusion it ends in. So, analyzing “Skepticism” its existence, different forms and contexts, and connection to Gothic fiction is the main motive of this research.